Synergistic activity of a novel class of azoimidazole dyes with polyvinylpyrrolidone-silver nanoparticles for the development of antibacterial textiles - Ribeiro, Ana Isabel Ferreira (2022)
The high demand for novel antimicrobial textiles by the medical, health care, hygiene, sportswear, personal protective equipment, and filtration sectors promoted the growth of functional textiles. However, the efficacy of antimicrobial agents against different pathogens is a considerable challenge due to the distinctive mechanisms of action and resistance. The development of novel synergistic antimicrobial agents may offer numerous opportunities to enhance antimicrobial effectiveness, namely boost the activity of individual agents, reduce dosages, minimize toxicity, and amplify the activity spectrum. On the one hand, azo dyes containing a heterocycle present good tinctorial strength and brightness of shades. In particular, the imidazole ring also has interesting antimicrobial, analgesic, and anti-inflammatory properties. On the other hand, silver nanoparticles (AgNPs) are renowned antimicrobial agents against a wide range of microorganisms, but their application is limited by the toxicity observed for effective concentrations. In this work, a novel class of azoimidazoles (AzoIz) and corresponding precursors (AmIz) were conjugated with polyvinylpyrrolidone-coated AgNPs, and their synergistic effect was assessed against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The results showed interesting antimicrobial properties of the novel AzoIz molecules when combined with a very small concentration of AgNPs. Thus, the application of these conjugates in textiles may lead to highly colored materials with remarkable antimicrobial properties, which worth to be further explored.